Hubungan Antara Usia Dengan Preeklampsia Pada Ibu Hamil Di POLI KIA RSUD Kefamenanukabupaten Timor Tengah Utara - Etika Desi Yogi; Hariyanto Hariyanto; Elfrida Sonbay (Akbid Harapan Mulya Ponorogo, 2018)
According to data from the North Central Timor Regency Health Office. The number of maternal deaths in 2011 were 12 people from 7000 live births. The direct causes of death such as preeclampsia/eclampsia were 5%, 50% bleeding, infection was 17%, other causes as many as 28%, the data from Poly KIA Kefamenanu Hospital in 2011 from 600 pregnant women were examined, pregnant women with preeclampsia as many as 35 people. Purpose of this study was to determine the relathionship between age and preeclampsia in pregnant women in the district Kefamenanu Poly KIA Hospital North Central Timor. Type of research is correlational analytic study with retrospective design. Population in this study were all pregnant women in the district Kefamenanu, Poly KIA Hospital North Central Timor in January to desember 2011, the sampling size were of 35 people, with a total population sampling technique. While research conducted during January to February 2013. Variable studied were age (independen), and preeclampsia (dependen). Method of data collection for the variables of age and preeklamsia variables using the data on Medical Record documentation in Poly KIA, to analyze the relationship between two variables using a statistical test contingency coefficient. The majority of women aged > 35 years (63,0%), almost entirely (83,0%) mild preeclampsia. Analyze of research data obtained using the Contingency coefficient test probability(ρ)=0,039≤ ɑ (0,05), which means there is a relationship between age and preeclampsia in pregnant women in the district kefamenanu Poly KIA Hospital North Central Timor with a low level of closeness (contingency coefficient=0,330). Mother is expected to increase the knowledge that age is one of facto: that can causes preeclampsia, so mothers are able to detect early if there is a danger sign/complications.